ANALISIS PERBAIKAN TANAH PADA PERLUASAN APRON BANDARA A.P.T PRANOTO SAMARINDA DENGAN METODE KOLOM GROUT MODULAR - Mahrus Efendi; Tukimun, Tukimun; Wahyu Mahendra (Media Bina Ilmiah, 2025)
This research aims to analyze the development needs of A.P.T Pranoto Samarinda Airport in accommodating the growth of air traffic, with a focus on apron expansion to increase aircraft parking capacity. This study also examines the use of pile foundations to improve the bearing capacity of the subgrade at the planned apron expansion site, considering the airport's location in a swampy and water catchment area. This research uses secondary and primary data analysis, including aircraft movement data, soil characteristics, and applicable regulations in the field of aviation. By using a modular grout column type foundation at the planned location for widening the apron at A.P.T Pranoto Samarinda Airport, a rigidclusion foundation diameter of 0.32 meters and 0.42 meters can be used with a planned depth of 12 to 18 meters. The results of this study are expected to provide appropriate recommendations for the development of A.P.T Pranoto Samarinda Airport, to improve service capabilities and operational safety.